Analisis Kandungan Fitokimia dan Aktivitas Antioksidan Daun Ciplukan (Physalis angulata L.) Berdasarkan Ketinggian Tempat Tumbuh - Marpaung, Rivaldi Ariansah; Edi, Syahmi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the differences in secondary metabolite content and antioxidant activity in the extract of ground cherry leaves grown in two locations with different altitudes. This study was designed with a descriptive experimental study. The research parameters carried out in the study were secondary metabolite compounds resulting from GC-MS (Gas Chromatography-Mass Spectrometry) analysis and IC50 values ​​were measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results showed differences in the content of secondary metabolite compounds and IC50 values ​​of antioxidant activity based on the altitude of the growing place. The extract of lowland ground cherry leaves (Kisaran) produced 13 compounds with a tendency towards carbohydrate/sugar derivatives, such as Melezitose. Meanwhile, the extract of highland leaves (Parongil) produced 11 compounds with a tendency towards alkane derivatives, including Phytol. There was no difference in antioxidant activity influenced by the part of the plant and the altitude of the growing place. The Kisaran ground cherry leaf extract with an IC50 value of 54.46 ppm and the Parongil ground cherry leaf extract with an IC50 value of 98.82 ppm are included in the strong antioxidant activity category. Meanwhile, the Kisaran ground cherry fruit extract with an IC50 value of 120.38 ppm and the Parongil ground cherry fruit extract with an IC50 value of 127.65 are included in the moderate antioxidant activity category.